Deep Learning Based Homomorphic Secure Search-Able Encryption for Keyword Search in Blockchain Healthcare System: A Novel Approach to Cryptography - Ali, Aitizaz; Pasha, Muhammad Fermi; Ali, Jehad; Fang, Ong Huey; Masud, Mehedi; Jurcut, Anca Delia; Alzain, Mohammed A. (Sensors, 2022)
Due to the value and importance of patient health records (PHR), security is the most critical feature of encryption over the Internet. Users that perform keyword searches to gain access to the PHR stored in the database are more susceptible to security risks. Although a blockchain-based healthcare system can guarantee security, present schemes have several flaws. Existing techniques have concentrated exclusively on data storage and have utilized blockchain as a storage database. In this research, we developed a unique deep-learning-based secure search-able blockchain as a distributed database using homomorphic encryption to enable users to securely access data via search. Our suggested study will increasingly include secure key revocation and update policies. An IoT dataset was used in this research to evaluate our suggested access control strategies and compare them to benchmark models. The proposed algorithms are implemented using smart contracts in the hyperledger tool. The suggested strategy is evaluated in comparison to existing ones. Our suggested approach significantly improves security, anonymity, and monitoring of user behavior, resulting in a more efficient blockchain-based IoT system as compared to benchmark models.
Keywords: Block-chain; Deep learning; Health records; Healthcare systems; Ho-momorphic encryptions; Homomorphic-encryptions; Keyword search; Patient health; Privacy; Security; Blockchain; Data Management; Deep Learning; Delivery of Health Care; Health Records, Personal; Humans; Access control; Blockchain; Deep learning; Homomorphic encryption; Privacy; Security; Smart contracts